Influence of Proprioceptive Inputs and Force Feedback Modality on Force Reproduction Performance - Eşrefoğlu, Alp; Henry, Mélanie; Baudry, Stéphane (Journal of motor behavior, 2024)
The sense of force can be assessed using a force reproduction task (FRT), which consists of matching a target force with visual feedback (TARGET phase) and reproducing it without visual feedback (REPRODUCTION phase). We investigated the relevance of muscle proprioception during the TARGET phase (EXP1) and the influence of the sensory source used for the force feedback (EXP2). Accordingly, EXP1 compared the force reproduction error (RE) between trials with (LV) and without (NoLV) local tendon vibration applied on the first dorsal interosseous during the TARGET phase, while EXP2 compared RE between trials performed with visual (VISIO) or auditory (AUDIO) feedback. The FRT was performed with the index finger at 5% and 20% of the maximal force (MVC). RE was greater with LV compared with NoLV at 5% (p = 0.004) but not 20% MVC (p = 0.65). The involvement of muscle proprioception in RFT was further supported by the increase in RE with LV frequency (supplementary experiment). RE was greater for VISIO than AUDIO at 5% (p < 0.001) but not 20% MVC (p = 0.054). This study evidences the relevance of proprioceptive inputs during the target PHASE and the influence of the force feedback modality on RE, and thereby on the assessment of the sense of force.